Economic Crisis and Portuguese National Health Service Physicians: Findings from a Descriptive Study of Their Perceptions and Reactions from Health Care Units in the Greater Lisbon Area - Inês Rego; Giuliano Russo; Luzia Gonçalves; Julian Perelman; Pedro Pita Barros (Acta Médica Portuguesa, 2017)
Introduction: In Europe, scant scientific evidence exists on the impact of economic crisis on physicians. This study aims at understanding the adjustments made by public sector physicians to the changing conditions, and their perceptions on the market for medical services in the Lisbon metropolitan area. Material and Methods: A random sample of 484 physicians from São José Hospital and health center groups in Cascais and Amadora, to explore their perceptions of the economic crisis, and the changes brought to their workload. This paper provides a descriptive statistical analysis of physicians’ responses. Results: In connection to the crisis, our surveyed physicians perceived an increase in demand but a decrease of supply of public health services, as well as an increase in the supply of health services by the private sector. Damaging government policies for the public sector, and the rise of private services and insurance providers were identified as game changers for the sector. Physicians reported a decrease in public remuneration (- 30.5%) and a small increase of public sector hours. A general reduction in living standard was identified as the main adaptation strategy to the crisis. Passion for the profession, its independence and flexibility, were the most frequently mentioned compensating factors. A percentage of 15% of physicians declared considering migration as a possibility for the near future. Discussion: The crisis has brought non-negligible changes to physicians’ working conditions and to the wider market for medical services in Portugal. Conclusion: The physicians’ intrinsic motivation for the professions helped counterbalance salary cuts and deteriorating working conditions.